Vivências cotidianas de crianças no Serviço de Convivência e Fortalecimento de Vínculos do Departamento Social Santa Júlia Billiart - Freitas, Liana Ferreira (2015)
This thesis aims to understand both the daily experiences of children addressed by the Interactional and Strengthening of Bonds Program (ISBP) and its impact on their interaction with family and school. It also attempts to assess the dynamics experienced by the children taking part in the activities provided by the program as well as what the project means to them. It starts by addressing the socio-historical context in which the process of social work was solidified and became public policy. In addition, it interfaces childhood and youth policies and highlights the legal achievements that contributed to the establishment of ISBP. The children´s daily experiences in the ISBP program are enriched by the nine to eleven year old´s narratives along with accounts by their families, who participated in the activities provided by the Departamento Social Santa Julia Billiart, an organization that provides social service and the ISBP program at Ipiranga, São Paulo (SP). This is a qualitative research, which is taken together with the children´s stories. Through the eyes and voices of the children, these narratives allow an immersion into their experiences regarding ISBP. This information demonstrates the meaning and the implications of the program for their lives. Among the meanings assigned, it is possible to verify that these experiences introduce children to a process of socialization, to the construction and strengthening of bonds when interacting with others, to acquisition and exchange of knowledge. In addition, in the parents´ eyes, the program is a secure environment that affects both the children and their families as well as those close to them. The narratives also show that such experiences have a positive impact on the lives of the children. The socio-educational, sociocultural and recreational activities developed in this environment enhance personal and social achievements; it is an open space where families and the community can socialize as well as, strengthen the bonds of familiar and social belonging. The quality of life for those involved is directly influenced by each one of these factors and results in the guarantee of the benefits from the National Policy for Social Assistance 2004